2018
DOI: 10.1002/phar.2083
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Intervention for Blood Pressure Control in Patients with Diabetes and/or Chronic Kidney Disease

Abstract: This study demonstrated that a physician-pharmacist collaborative intervention was effective in reducing mean systolic BP and improving BP control in patients with uncontrolled hypertension with DM and/or CKD, regardless of which BP guidelines were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
(56 reference statements)
1
35
0
Order By: Relevance
“…The customized care plan was designed and delivered to the patients on monthly basis based on the condition and need of the patient by the WHO-FIP Pharmaceutical care model. (2) The QoL was assessed using validated KDQoL-36 instrumentUsual care (n = 75)The HRQoL scores were significantly improved over time in the domains noticed with regard to the “physical functioning, general health, emotional well-being, social functioning, symptom/problem list, and effects of kidney disease” in all the three centres of PC group compared to UC group with p < 0.05The baseline HRQoL score of KDQoL-36 domains such as ESRD-targeted areas were not significantly different in the UC group versus PC group in all the three HD centresThe pharmaceutical care provided by a trained pharmacist had positive impact in HRQoL of HD patientsAnderegg et al (2018)USA [54]Cluster randomised trial32 medical offices from 15 statesTo determine if hypertensive patients with comorbid DM and CKD receiving a pharmacist intervention had improved BP control and greater reduction in mean BP at 9 months compared with those receiving usual care227 patientsIntervention group 61.7 (11.6), control 63.1 (12.2)Pharmacist interviewed patients to review medications, assessed knowledge and then educated the patients on HTN. Individualised care plans were prepared and presented to the physician108 patientsIntervention group had significantly greater mean systolic blood pressure reduction compared with usual care at 9 months (8.64 mm Hg; 95%, CI − 12.8 to − 4.49, p < 0.001).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The customized care plan was designed and delivered to the patients on monthly basis based on the condition and need of the patient by the WHO-FIP Pharmaceutical care model. (2) The QoL was assessed using validated KDQoL-36 instrumentUsual care (n = 75)The HRQoL scores were significantly improved over time in the domains noticed with regard to the “physical functioning, general health, emotional well-being, social functioning, symptom/problem list, and effects of kidney disease” in all the three centres of PC group compared to UC group with p < 0.05The baseline HRQoL score of KDQoL-36 domains such as ESRD-targeted areas were not significantly different in the UC group versus PC group in all the three HD centresThe pharmaceutical care provided by a trained pharmacist had positive impact in HRQoL of HD patientsAnderegg et al (2018)USA [54]Cluster randomised trial32 medical offices from 15 statesTo determine if hypertensive patients with comorbid DM and CKD receiving a pharmacist intervention had improved BP control and greater reduction in mean BP at 9 months compared with those receiving usual care227 patientsIntervention group 61.7 (11.6), control 63.1 (12.2)Pharmacist interviewed patients to review medications, assessed knowledge and then educated the patients on HTN. Individualised care plans were prepared and presented to the physician108 patientsIntervention group had significantly greater mean systolic blood pressure reduction compared with usual care at 9 months (8.64 mm Hg; 95%, CI − 12.8 to − 4.49, p < 0.001).…”
Section: Resultsmentioning
confidence: 97%
“…Many studies reported pharmacists’ interventions in: modifying drug doses and recommending new pharmacotherapy; [ 16 , 19 , 21 – 23 , 25 – 27 , 29 , 30 , 32 40 , 52 , 59 ]; interacting with a member of the multidisciplinary team; [ 15 17 , 19 21 , 23 – 25 , 27 , 31 , 32 , 34 38 , 40 43 ] requesting and monitoring laboratory parameters; [ 15 , 23 , 25 , 27 , 33 , 34 , 36 , 37 , 43 ] assessing appropriateness of medications prescribed for hospitalised patients at each point of care; [ 17 , 22 , 29 , 30 , 35 38 , 40 , 57 ]. Fewer studies described pharmacist processes at out-patient, pharmacist-led clinics relating to the management of specific CKD complications, such as anaemia; [ 34 , 39 , 44 ] hypertension and diabetes; [ 54 ] managing hypertension through telemedicine; [ 41 ] optimising dyslipidaemia management; [ 37 , 45 ] improving haemoglobin A1c levels (HbA1c); [ 43 ] and emphasising smoking cessation. [ 37 , 43 ] Development of protocols and compiling and updating guidelines were also described in two studies [ 22 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies aimed to (a) achieve close collaboration among medical staff, (b) adequately review therapeutic interventions and (c) improve patient adherence to HTN treatment. In particular, pharmacists played a principal role in assessing the HTN medication regimen 10‐14 …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…There are numerous randomized controlled trials of pharmacist‐led and interdisciplinary interventions investigating the impact on BP reduction, BP control rates, and reduced cardiovascular risk 10,12,13,24,28‐33 as well as several systematic reviews and meta‐analyses published 34‐37 . These data indicate that compared with usual BP management, interventions by pharmacists working in community pharmacies were associated with clinically important improvement in BP control, whether or not hypertension was associated with cardiovascular comorbidities.…”
Section: Discussionmentioning
confidence: 99%